Elucidation of seed dormancy and phytohormones by germination after exogenous foliage whey application - Mulam, Khot Vidhesh, Jadhav Rajesh K, Pranay (Journal of Plant Stress Physiology)
A study was conducted with an aim of achieving 100% seed germination and to evaluate the rate of dormancy upon exogenous application of the deproteinised leaf juice (DPJ) in various leguminous and non leguminous seeds. DPJ if inducing retardation of dormancy, the activity of enzyme was analysed to prove the presence of phytohormones. DPJ from the three non leguminous foliages of brinjal, radddish and dasheen were prepared by green crop fractionation. The seed germination results obtained by the paper towel method and the activity of enzyme protease in DPJ of radish and Colocasia leaves separately. There was variation in germination rate by different DPJ influence. Some seeds showed fast germination while some germinated late. Few seeds were not germinated by control. In some seeds, DPJ decreased the rate of germination while on the contrary there was rapid growth of seedlings by the potentiality of DPJ. DPJ found mutagenic by its influencing inhibitory expression in seedling growth in some cases. The enzyme protease released by phytohormone gibberellin during the seed germination. Positive glyoxlic test indicated presence of auxins in whey.